To Produce an Effective Composition of Vermiculite Plita and to Study the Coefficient of Thermal Conductivity (The Peerian Journal, 2022)
This paper discusses the development of an effective composition of extra-light concretes based on foamed vermiculite and its thermal conductivity coefficient.